Immunomodulatory properties of human placental mesenchymal stem/stromal cells. (November 2017) - Abumaree, M.H.; Abomaray, F.M.; Alshabibi, M.A.; AlAskar, A.S.; Kalionis, B.
Abstract: Mesenchymal stem/stromal cells (MSCs) are isolated from various fetal and adult tissues such as bone marrow, adipose tissue, cord blood and placenta. Placental MSCs (pMSCs), the main focus of this review, are relatively new MSC types that are not as intensively studied compared with bone marrow-derived MSCs (BMMSCs). MSCs modulate the immune functions of important immune cells involved in alloantigen recognition and elimination, including antigen presenting cells (APCs), T cells, B cells and natural killer (NK) cells. Clinical trials, both completed and underway, employ MSCs to treat various human immunological diseases, such as multiple sclerosis (MS) and type 1 diabetes. However, the mechanisms that mediate the immunosuppressive effects of pMSCs are still largely unknown, and the safety of pMSC use in clinical settings needs further confirmation. Here, we review the current knowledge of the immunosuppressive properties of placental MSCs. Highlights: Mesenchymal stem/stromal cells (MSCs) are isolated from various fetal and adult tissues such as bone marrow, adipose tissue and placenta. Placental MSCs (pMSCs) are relatively new MSC types that are not as intensively studied compared with BMMSCs. MSCs modulate the immune functions of important immune cells involved in alloantigen recognition and elimination, including APCs, T cells, B cells and NK cells. Clinical trials, both completed and underway, employ MSCs to treat various human immunological diseases, such as MS and type 1 diabetes. However, the mechanisms that mediate the immunosuppressive effects of MSCs are still largely unknown, and the safety of MSC use in clinical settings needs further confirmation. Here, we review the current knowledge of the immunosuppressive properties of MSCs from placenta.